2021
DOI: 10.1186/s12934-021-01617-z
|View full text |Cite
|
Sign up to set email alerts
|

Customized yeast cell factories for biopharmaceuticals: from cell engineering to process scale up

Abstract: The manufacture of recombinant therapeutics is a fastest-developing section of therapeutic pharmaceuticals and presently plays a significant role in disease management. Yeasts are established eukaryotic host for heterologous protein production and offer distinctive benefits in synthesising pharmaceutical recombinants. Yeasts are proficient of vigorous growth on inexpensive media, easy for gene manipulations, and are capable of adding post translational changes of eukaryotes. Saccharomyces cerevisiae is model y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 169 publications
0
36
0
4
Order By: Relevance
“…Lastly, recent studies suggested S. pombe could find novel applications in biotechnology, including winemaking (Benito et al, 2016) and flavour formation during food fermentations (Du et al, 2021), but also as a possible cell factory (Madhavan et al, 2021). S. pombe ’s ability to grow in environments with low water activity, high alcohol content, very low pH and a wide range of temperatures (Loira et al, 2018) make it an attractive, and perhaps underutilized, biotechnological tool.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, recent studies suggested S. pombe could find novel applications in biotechnology, including winemaking (Benito et al, 2016) and flavour formation during food fermentations (Du et al, 2021), but also as a possible cell factory (Madhavan et al, 2021). S. pombe ’s ability to grow in environments with low water activity, high alcohol content, very low pH and a wide range of temperatures (Loira et al, 2018) make it an attractive, and perhaps underutilized, biotechnological tool.…”
Section: Discussionmentioning
confidence: 99%
“…Y. lipolytica also has an operational secretory system with which it releases huge quantities of enzymes, such as lipases [ 196 ] and proteases [ 197 ], and heterologous proteins [ 27 , 198 , 199 , 200 , 201 , 202 ] for industrial applications. Among the more than 100 recombinant proteins produced by engineered Y. lipolytica [ 202 ], there are several pharmaceutically important human-compatible bio-compounds secreted by ‘humanized’ strains, including interferon alpha 2b [ 203 ], epidermal growth factor [ 204 ], N -glycoproteins [ 205 , 206 ], blood coagulation factor XIIIa [ 207 ], proinsulin and insulinotropin [ 208 ], cytochrome P450 [ 209 ], estrogen receptor α [ 210 ], and anaphylatoxin C5a that possesses both spasmogenic and leukocyte-related properties [ 211 ].…”
Section: Added-value Compounds For Industrial Applicationmentioning
confidence: 99%
“…In biopharmaceutical terms, these molecules are specifically produced under biotechnological processes based on genetically engineered organisms used as an expression host [ 4 ]. The main organisms used here are bacteria, yeast, mammalian cells, and insect cells, with each system having their own advantages as well as limitations [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%